The Making of Jewish Universalism : From Exile to Alexandria. - Simkovich, Malka (Lexington Books, 2016)
Interest in Jewish universalism is on the rise, yet scholars lack a common definition of the concept. This book advocates for a common definition of universalism as it applies to an Early Jewish context and traces the origins of Jewish universalist thought from the prophetic literature of the Hebrew Bible through the period of the Second Temple.